OPTIMASI PENGELOLAAN DAN PENGAWASAN PRAKTIKUM DI LABORATORIUM KOMPUTASI PROGRAM STUDI TEKNIK INFORMATIKA FAKULTAS TEKNIK UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Wrahatnala, Ery Sadewa Yudha; Septi H, Velek Aditya (Informatics, Universitas 17 Agustus 1945 Surabaya, 2015)
For a program of study, the laboratory is one of the infrastructure to increase student competency. The task of each laboratory practicum one of which is held to be conducted every semester. Computing Laboratory in carrying out practical work using computers to increase student competence to do with programming capabilities.Â In order to achieve the objectives that were set up from any lab work, it is necessary to good management and supervision in its implementation. Therefore, to assist the management and supervision of this, it should be made a tool in the practical implementation in Laboratoium Computing.Â With the Remote Desktop Application To Computing Laboratory is expected to help improve the quality of practical implementation. This application can be used for purposes of monitoring and supervision of the use of computers in a lab. One of the forms of violations committed in following the practicum students are using computers that are not in accordance with practical needs. Remote Desktop application is expected to help overcome these problems, especially those related to restrictions on the use of applications, timing of lab work, and also for the practical assessment. In the end, the utilization of remote desktop applications are expected to help the performance of the Computing Laboratory in carrying out practical work in each semester.Keywords : Remote Desktop, Management and Supervision, Practical, Laboratory